2022
DOI: 10.3390/coatings12111695
|View full text |Cite
|
Sign up to set email alerts
|

Manufacture and Characterization of Geopolymer Coatings Deposited from Suspensions on Aluminium Substrates

Abstract: Geopolymers compete with a number of conventional coatings and a few of them have already been replaced. The aim of this work was the analysis of alkali-activated metakaolin-based geopolymers and their use as brush-applied coatings, which were chosen due to their simplicity and cost-effectiveness. Eight coatings were prepared and the AlMgSi aluminum alloy underlying the substrate was also studied. The main characterizations of the prepared coatings were the microscopy analysis, which showed that manual paintin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 42 publications
1
16
1
Order By: Relevance
“…This work follows our previous research [23,24] and expands our knowledge about the selected single-and multi-layer GP coatings with different applications by brushes and some types of curing processes. We observed changes in the visual quality of the prepared GP coatings and changes in their mechanical properties.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…This work follows our previous research [23,24] and expands our knowledge about the selected single-and multi-layer GP coatings with different applications by brushes and some types of curing processes. We observed changes in the visual quality of the prepared GP coatings and changes in their mechanical properties.…”
Section: Introductionmentioning
confidence: 64%
“…The GP coating was selected based on our previous research [23,24]. The selected GP had good properties, which was a good starting point for the following complex research creating multi-layer GP coatings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thys suspensions is usable for insoluble heat and corrosion resistant coatings. Our previous research also shown that the selected geopolymer suspensions adhesion was at a very high level [17]. The fire resistance of geopolymer suspensions for non-metallic substrates was analyzed on XPS and DTD substrates.…”
Section: Discussionmentioning
confidence: 95%
“…For the geopolymer mixtures geopolymerization occurs at elevated temperatures, in contrast to mixtures with a different composition, where geopolymerization can occur at lower temperature [19,20]. For the selected geopolymer mixtures, it is necessary to reach a certain minimum temperature, which was experimentally determined to be 170 °C [21]. This temperature is important parameter influencing the resulting quality of the coatings.…”
Section: Fig 1 Scheme Of Preparation Gp Coatings and Measurment Of Al...mentioning
confidence: 99%